The impact of body image disturbances on social avoidance in burn patients - Huang, Qingjiang; Li, Zhujing; Yue, Fengwen; Shi, Weitian; Lei, Ying; Jiang, Ting (Frontiers in Psychiatry, 2025)
BackgroundBody image serves as an auxiliary to nonverbal communication, facilitating the transmission of nonverbal information in interpersonal interactions. However, burn patients often experience body image disturbances due to scarring, skin pigmentation changes, and functional impairments, leading to communication difficulties and social anxiety. Regrettably, this phenomenon has received limited in-depth exploration in previous research.MethodsTo address this gap, this study, based on the fear-avoidance model, randomly recruited 286 patients to analyze the impact of body image disturbances on social avoidance and its internal mechanisms.ResultsThe experimental results demonstrated that burn patients with higher levels of body image disturbances exhibited stronger tendencies toward social avoidance. In this process, psychological resilience could mitigate the adverse effects of body image disturbances on social avoidance by enhancing individuals’ adaptability. Burn patients with high family support often exhibited more positive cognitions of their body image, enhanced their psychological resilience, and improved their social avoidance.ConclusionThis study further deepened and expanded the fear-avoidance model by proposing a collaborative intervention framework involving family support and psychological resilience. These findings offer new practical suggestions for clinical practitioners and family members to enhance the interpersonal communication skills of burn patients.